Language-based information-flow security - Sabelfeld, A.; Myers, A.C. (IEEE journal on selected areas in communications, 2003)
Current standard security practices do not provide substantial assurance that the end-to-end behavior of a computing system satisfies important security policies such as confidentiality. An end-to-end confidentiality policy might assert that secret input data cannot be inferred by an attacker through the attacker's observations of system output; this policy regulates information flow. Conventional security mechanisms such as access control and encryption do not directly address the enforcement of information-flow policies. Previously, a promising new approach has been developed: the use of programming-language techniques for specifying and enforcing information-flow policies. In this paper, we survey the past three decades of research on information-flow security, particularly focusing on work that uses static program analysis to enforce information-flow policies. We give a structured view of work in the area and identify some important open challenges.